Sarcopenia and Cardiovascular Diseases in Individuals With Diabetes or Prediabetes - Xia Wang; Qingyue Zeng; XiJie Yu; Shuangqing Li (The Journal of Clinical Hypertension)
ABSTRACT Sarcopenia is a known risk factor for cardiovascular disease (CVD) in individuals with diabetes or prediabetes, but the impact of changes in sarcopenia status on CVD risk remains unclear. This study aimed to examine how changes in sarcopenia status between baseline and the second follow‐up survey, conducted 2 years later, influence the risk of developing incident CVD. Incident CVD was identified based on self‐reported physician diagnoses of heart disease, such as angina, myocardial infarction, heart failure, or stroke. Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for potential confounders. The results showed that participants who progressed from non‐sarcopenia to possible sarcopenia or sarcopenia had a higher risk of developing CVD. Their risk was significantly greater compared to those who remained non‐sarcopenic (HR 1.37, 95% CI 1.08–1.73). Conversely, individuals who recovered from sarcopenia to non‐sarcopenia or possible sarcopenia had a lower risk of CVD. Their risk was lower than those who remained sarcopenic (HR 0.40, 95% CI 0.20–0.82). Among individuals with possible sarcopenia at baseline, those who recovered to non‐sarcopenia had a reduced CVD risk. This reduction was significant compared to those who remained in possible sarcopenia (HR 0.62, 95% CI 0.46–0.84). These findings suggest that changes in sarcopenia status have a significant impact on CVD risk, with worsening sarcopenia increasing the likelihood of CVD and recovery lowering the risk in individuals with diabetes or prediabetes.